2017
DOI: 10.1177/0003489417727014
|View full text |Cite
|
Sign up to set email alerts
|

Does Snoring Time Always Reflect the Severity of Obstructive Sleep Apnea?

Abstract: The change in snoring rate according to the severity of AHI showed an inverted U-shaped pattern, with a peak in the moderate OSA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although we revealed that employing snoring rate and snoring index resulted in correlations with AHI values determined from PSG, the estimate of correlations was less than others (STII, snoring frequency, and snoring intensity). This may be due to the deviation between the correlations, such as the negative r (-0.04) in Hong’s study 14 as well as the lower correlations (0.04) in Levartovsky’s study 20 and Alshaer’s study 19 (0.32). Another explanation might be the limited number of studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although we revealed that employing snoring rate and snoring index resulted in correlations with AHI values determined from PSG, the estimate of correlations was less than others (STII, snoring frequency, and snoring intensity). This may be due to the deviation between the correlations, such as the negative r (-0.04) in Hong’s study 14 as well as the lower correlations (0.04) in Levartovsky’s study 20 and Alshaer’s study 19 (0.32). Another explanation might be the limited number of studies.…”
Section: Discussionmentioning
confidence: 93%
“…According to acoustic analysis methods, we classified these 13 studies into 5 subgroups. The first subgroup contained studies that analyzed snoring rate (or snoring duration); 3 studies reported correlations between snoring rates (snoring duration divided by total sleep time) and the AHI [14][15][16] . In these 3 studies, snore sensors were used to record snoring sounds during sleep.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while comparing the snoring rates between the groups (divided according to the severity of OSAS by AHI), they found that the snoring rates increased as the AHI increased from the control to the moderate OSAS group and decreased as the AHI increased from the moderate to the very severe OSAS group. [ 12 ] Most of the studies proved that there is an association between snoring intensity and the severity of OSAS and reported a positive correlation between the intensity of snoring sound and AHI; therefore, they showed that snoring became louder as OSAS became more severe. [ 4 19 20 21 ] Acar et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of opioids and other sedating medications, tidal volume or depth of breath may be shallow, and rhythm may be irregular representing pharyngeal collapsibility/apneic events (Al-Khabori et al, 2014;Drummond et al, 2013). Clinicians should use their auditory senses to listen for snoring, which is a sign of varying degrees of pharyngeal collapse (Alakuijala & Salmi, 2016;Hong et al, 2017;Koo et al, 2017). Much like patients with OSA, patients experiencing OIUAS and OIRD could exhibit noisy breathing and a distinct pattern with pause in breaths for more than 10 seconds, then a louder snore as they arouse to open their airway .…”
Section: Sedation Scalesmentioning
confidence: 99%